Forget what you know about RCAA2: now you are RDA - Chacón M., Ana Victoria (2010)
It presents a brief overview of what is involved in cataloguing materials with the Anglo-American Cataloguing Rules and the changes that will be generated with the use of the new GDR. In addition, it points out the importance of introducing new terms such as: work, expression, manifestation and item.